Exploring Problem-Based Learning Impact on Students’ Motivation and Engagement in an e-Course Utilizing Microsoft Teams. - Bourdas, Konstantinos; Kiriakaki, Georgia; Grigori, Maria; Themeli, Anastasia; Kytagias, Christos; Psaromiligkos, Yannis (Journal of Integrated Information Management, 2025)
Purpose—The COVID-19 pandemic has rapidly accelerated the implementation of e-learning across all levels of education. However, maintaining high levels of student motivation and engagement is a real challenge in a Technology-Enhanced Learning Environment (TELE), as the use of technology alone is a significant source of distraction. To address this challenge, at the Department of Business Administration at the University of West Attica, an e-course that utilizes a Problem-Based Learning (PBL) method that was delivered via the Microsoft Teams platform, was designed and implemented. Drawing on this conceptual framework, the primary aim of this study is to investigate the effect of PBL on students' motivation and engagement, as well as to explore students' perceptions of the PBL method. Design/methodology/approach—A quasi-experimental pretest–posttest design was adopted in this study. Data were collected from 162 students using Microsoft Teams analytics and the Motivated Strategies for Learning Questionnaire (MSLQ), which was administered both before and after the completion of the e-course. To assess students’ motivational orientations, a modified version of the MSLQ was employed, incorporating dimensions such as intrinsic goal orientation, extrinsic goal orientation, and self-efficacy for learning and performance. Students’ perceptions of the PBL method were evaluated through open-ended questions, and their responses were analyzed using an inductive content analysis technique. Findings—The analysis of the results reveals that our proposed e-course design approach enhances students' intrinsic motivation, self-efficacy, and engagement. Additionally, these findings are further supported by students' perceptions of working with the PBL method. Originality/value—This study, despite its limitations, provides valuable insights into the limited research on the customization of the Microsoft Teams platform from a pedagogical perspective to facilitate complex teaching methods, such as the PBL method.